Reactive oxygen species mediate bioeffects of static magnetic field via impairment of long-chain fatty acid degradation in Escherichia coli - Li, Haodong; Fang, Yanwen; Huang, Jirong (Frontiers in Microbiology, 2025)
Static magnetic fields (SMF) have been shown to influence bacterial growth via reactive oxygen species (ROS). However, the underlying mechanisms remain poorly understood. This study investigated the role of ROS in mediating the growth inhibitory effect of SMF on Escherichia coli. We demonstrated that exposure of bacteria to a 250 mT SMF significantly elevates ROS level, as confirmed by a chemical fluorescent probe, electron paramagnetic resonance (EPR) spectroscopy, and a genetically engineered redox biosensor. Transcriptomic analysis revealed that SMF- and hydrogen peroxide (H2O2) treatments share a set of common differentially expressed genes (DEGs), particularly those involved in long chain fatty acid metabolism, the tricarboxylic acid (TCA) cycle, and defense mechanisms against ROS stress. Specifically, SMF downregulates the expression of the fadD gene, impairing long-chain fatty acid (LCFA) degradation, which is critical for bacterial growth. Interestingly, overexpression of the superoxide dismutase gene SodB alleviated SMF-induced growth inhibition, highlighting the pivotal role of ROS in this process. Taken together, our findings provide novel insights into the molecular mechanism by which oxygen serves as a magnetic target, triggering ROS signaling, and enabling bacteria to adapt to SMF exposure.